Ukraine as a center of contemporary global religious confrontation: Constantinople – Rome – Moscow - Fylypovych, Liudmyla (Humaniora. Czasopismo Internetowe, 2020)
The article analyzes the historical and contemporary status of Ukrainian churches of the Eastern Christian tradition, which at the beginning of the 21st century found themselves at the epicenter of the geopolitical confrontation between the three world’s Christian centers. Being a border area between Europe and Asia, Ukraine always had to make choices of the ways of its civilizational development. There were periods in its history when Ukraine did so voluntarily, becoming an independent center of the east Slavic, in particular, of the Eastern Christian world. However, the presence of aggressive neighbors made changes to the Kyiv-centric discourse of the country, inclining Ukrainians either to Constantinople, Rome or Moscow. Under these circumstances, the orientation towards the development of an independent and distinctive Kyiv Church was partially lost, but at the same time opposition to the world religious centers, which sought to determine the spiritual life of Ukrainians, formed. Ukraine now seeks to rectify the situation of subordination to the foreign centers and to get rid of colonial dependence on different countries and religions. Having received Tomos from the Patriarch of Constantinople in 2018, the united Ukrainian Local Orthodox Church will in time effectively and confidently influence the geopolitical situation in the world. The framework of the historical religious-political triangle will gradually be destroyed, and Ukraine will confidently declare its autonomous standing in the Christian oekumene.